1998
DOI: 10.1074/jbc.273.9.5101
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilament (NF) Assembly; Divergent Characteristics of Human and Rodent NF-L Subunits

Abstract: Previous studies have shown that rodent neurofilaments (NF) are obligate heteropolymers requiring NF-L plus either NF-M or NF-H for filament formation. We have assessed the competence of human NF-L and NF-M to assemble and find that unlike rat NF-L, human NF-L is capable of self-assembly. However, human NF-M cannot form homopolymers and requires the presence of NF-L for incorporation into filaments. To investigate the stage at which filament formation is blocked, the rod domains or the full-length subunits of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 47 publications
(46 reference statements)
3
51
0
Order By: Relevance
“…Previous studies using the Vim -cells have shown that rat and mouse neurofilament triplet proteins are obligate heteropolymers in vivo (Ching and Liem, 1993;Lee et al, 1993). In contrast, human NFL was shown to be able to selfassemble into filaments (Carter et al, 1998). This unique selfassembly property of hNFL was thought to be the result of the differences in the primary sequences between human and rodent NFL in the rod domain.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Previous studies using the Vim -cells have shown that rat and mouse neurofilament triplet proteins are obligate heteropolymers in vivo (Ching and Liem, 1993;Lee et al, 1993). In contrast, human NFL was shown to be able to selfassemble into filaments (Carter et al, 1998). This unique selfassembly property of hNFL was thought to be the result of the differences in the primary sequences between human and rodent NFL in the rod domain.…”
Section: Resultsmentioning
confidence: 84%
“…Effects of CMT2 mutations on hNFL self-assembly Human NFL has been reported to form homopolymers in vivo, as opposed to rat or mouse NFL (Carter et al, 1998). The authors noted that there were eight differences between rNFL and hNFL in the rod domain.…”
Section: Effects Of Rnfl Mutations In Nf Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…Neurons may also express other intermediate filament proteins, including nestin, synemin, syncoilin and vimentin (Perrin et al, 2005). Mouse NFH, NFM and NFL subunits are unable to selfassemble into homopolymer filaments, although -at least in vitro -human NFL can do so (Carter et al, 1998). Among the notable properties of NFs are their exceptionally long half-lives (Millecamps et al, 2007;Nixon and Logvinenko, 1986;Yuan et al, 2009) and their elastic fibrous properties that enable them to maintain the markedly asymmetrical shape of neurons (Wagner et al, 2007).…”
Section: Neurofilament Structure and Functionmentioning
confidence: 99%
“…Alternatively, failure to observe parallelism, and indeed some of the other validation parameters, could be in part due to some of the less practiced operators experiencing difficulty with interpretation or complexity of the plate plans and SOPs. It has been argued that as NfL has the tendency to re-aggregate following suspension [39][40][41][42] that delays in sample and standard incubation could account for the failure to satisfactorily measure NfL in many experiments 26 . The data show that between 15 and 60 minutes were taken, from the time standards were reconstituted, to incubate the standards and samples on the ELISA plates.…”
Section: Parallelismmentioning
confidence: 99%